Standardization of pegagan extract (Centella asiatica (L.) Urban) based on siaticoside content using TLCdensitometricmethod - S. Pramono; D. Ajiastuti (Indonesian Journal of Pharmacy, 2004)
In assuring people consuming herbal products of high standard and reliable quality, a standardization process was performed on an Indonesian herb namely pegagan (Centella asiatica (L.) Urban) from Kaliurang, Boyolali, and Tawangmangu regions emphasizing on asiaticoside contents as its active constituent.Process of standardization was initiated by searching the best solvent for extraction. Water, ethanol 30%, 50%, and 70% were used for maceration of the herb. Asiaticoside contents were then determined by TLC-densitometry. The result of research showed that ethanol 70 % could dissolve highest concentration of asiaticoside from pegagan herb so it was then used for larger scale extraction of three different plant materials. TLC-densitometric data showed that asiaticoside contents of pegagan herb originally from Kaliurang were 0.98 ± 0.13.%, Boyolali were 1.34 ± 0.20.%, and Tawangmangu were 0.21 ± 0.3 %.Key words: Centella asiatica (L.) Urban, asiaticoside, TLC-densitometry